Integration sicherer antriebsfunktionen nach norm IEC 62061 - Kayser, Karl-Heinz (НТУ "ХПІ", 2013)
The paper deals with implementation of safety regulations in electric drives. The basic criteria concerning technical systems safety required by IEC 62061 standard are outlined. It is shown how to apply these criteria relative to electric drive operation. Recommendations concerning technical implementation of safety functions in the hardware of electric drives’ control systems are given.

В статті йдеться про вимоги до безпечного функціонування електроприводів. Наведені основні чисельні показники безпеки функціонування згідно стандарту МЕК 62061. Показано, як наведені показники співвідносяться із функціонуванням елек- тропривода. Надані рекомендації щодо реалізації функцій безпеки в апаратному забезпеченні систем керування електроприводами.
Integration of IEC 62061 standard safety norms into electric drives